Assessment of heavy metal and radioactive element levels in the ovarian follicular fluid of pregnant and non-pregnant Kyrgyz breed mares. - Risvanli, Ali; Hatipoglu, Fatih; Salykov, Ruslan; Timurkaan, Necati; Kadiralieva, Nariste; Kasymalieva, Kaliyman K; Seker, Ibrahim; Jurakulov, Kobil; Ruzikulov, Nuriddin; Abdurasulov, Abdugani; Kalkan, Cahit (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: In the current study, we aimed to ascertain the levels of heavy metals and radioactive elements in the ovarian follicular fluids of pregnant and non-pregnant Kyrgyz mares. Materials and Methods: To this end, follicular fluids were obtained from 49 Kyrgyz mares aged 3–5 years. The mares were in various stages of pregnancy (Group 1, n = 27) or were non-pregnant (Group 2, n = 22). We measured the levels of cadmium (Cd), lead (Pb), mercury (Hg), antimony (Sb), cobalt (Co), potassium (K), uranium (U), nickel (Ni), and thorium (Th) in follicular fluids using atomic emission mass spectrometry. Subsequently, the data were statistically analyzed according to whether the mare was pregnant or not, the pregnancy stage, the presence or absence of the corpus luteum in the ovaries, the corpus luteum’s diameter if present, and the presence or absence and diameter of follicles. Results: We found that K levels were higher in non-pregnant mares (0.00564 ± 0.000590 ppm, p = 0.009). Furthermore, Ni (0.01033 ± 0.001880 ppm, p = 0.07) and K (0.00563 ± 0.000498 ppm, p = 0.026) levels were higher in mares with a follicle diameter of 1–3 cm. However, these results did not change according to the month of pregnancy, number of follicles, presence or absence of the corpus luteum in the ovaries, number of corpora lutea, and their diameters. Conclusion: Thus, we concluded that heavy metal and radioactive element levels in the ovarian follicular fluids of Kyrgyz mares do not significantly change with pregnancy status, and there are limited detrimental effects of pollution on the follicular fluids. J. Adv. Vet. Anim. Res., 11(3): 583-591, September 2024 http://doi.org/10.5455/javar.2024.k808